Mutation in the CREBBP Gene in the Girl with Toe Walking Syndrome: Clinical Case - David Pomarino; Anneke Thren; Johanna R. Thren; Kevin Rostasy; Anna A. Emelina (Вопросы современной педиатрии)
Baclground. Pathogenic variants of the CREBBP gene have been revealed in patients with Rubinstein-Taybi and Menke-Hennekam syndromes, however, the toe walking symptom was not mentioned in these pathologies.Clinical Case Description. The pathogenic nucleotide variant c.5600G>A in heterozygous state in the CREBBP gene was revealed in our 9-year-old female patient with refractory toe walking and developmental speech delay. There were no abnormalities typical for Rubinstein-Taybi syndrome, but there were several signs of Menke-Hennekam syndrome.Conclusion. The genetic anomaly associated with toe walking is described. This observation allows us to critically relate to the hypothesis about the idiopathic genesis of this form of gait disorder at the absence of obvious neurological or orthopedic causes of its development.